THE FLORA OF THE DRAKENSBERG ALPINE CENTRE - CARBUTT, C.; EDWARDS, T. J. (Edinburgh Journal of Botany, 2004)
The Drakensberg Alpine Centre (DAC) comprises the 40,000km2 high-altitude range of hills, mountain peaks and escarpment plateau bordering the eastern interior of southern Africa. Renowned for its species-rich flora and high levels of endemism, the DAC is here shown to support over 2800 specific and infraspecific native taxa, with c.16% of the angiosperm taxa being endemic, the latter equalling the flora of KwaZulu-Natal. Comparisons of the DAC's largest families and genera are made with those of the Cape Floral Region and KwaZulu-Natal, and the largest families are also compared with those of the Afromontane and Pondoland regions. In addition, comparisons are made between the high-altitude floras of southern and south-central Africa on the basis of their Cape element.
Keywords: Drakensberg Alpine Centre; endemism; floristics; high-altitude flora; radiation; southern Africa